Market Efficiency and the Legal Liability of Auditors: Comment. - Largay III, James A.; Paul, Jack W. (The Accounting Review, 1983)
ABSTRACT: In a provocative but rarely cited article, Anderson [1977] examined the potential implications of efficient capital markets research for auditors' legal liability under the common law. He concludes that if common law courts understand and apply the findings of efficient markets research in their deliberations, the class of potential plaintiffs may be enlarged, but auditors' overall economic liability for damages may be reduced. The present article criticizes certain of Anderson's conclusions in the common law context and questions the relevance of his analysis because (1) investors' suits against auditors of publicly-held companies generally are brought under federal statutory law–the Securities Act of 1933 and the Securities Exchange Act of 1934–and (2) the class of publicly-held securities investigated by efficient markets research is generally also subject to the 1934 Act. Some federal courts applying the 1934 Act have already implicitly acknowledged market efficiency by allowing plaintiffs to show indirect "market reliance" rather than prove direct reliance on a specific representation made by the auditor. Thus we find that introducing knowledge of market efficiency into the legal system will probably not have the far-reaching effects contemplated by Anderson.